Fundamentals of mass transfer and kinetics for biosorption of oil and grease from agro-food industrial effluent by Serratia marcescens SA30 - Fulazzaky, Mohamad Ali; Abdullah, Shakila; Salima, Mohd Razman (The Royal Society of Chemistry, 2015)
Fundamental studies of mass transfer and kinetics are essential for a detailed understanding of the characteristics and the mechanisms of biosorptions. In this study, the modified mass transfer factor models were used to assess the rates of global, external and internal mass transfer for the biosorption of oil and grease (O&G) from agro-food industrial effluent (AFIE) by Serratia marcescens SA30. Using a packed-bed column reactor to run the experiments at different O&G concentrations, this study finds that the global mass transfer rate increases exponentially accompanied with the sudden increase of the cell surface sorption. The influence of concentration on the external mass transfer is very remarkable due to the effects of driving force and biomass growth can lead to a rapid movement of O&G molecules from the bulk water to extracellular precipitation. The resistance to mass transfer could be dependent on intracellular accumulation at the beginning and then on film mass transfer at the final stage of biosorption of O&G by Serratia marcescens SA30. This study would provide a green and sustainable pathway for removing O&G from AFIE.